ANALISIS PERMINTAAN KEDELAI PADA INDUSTRI TEMPE DI KECAMATAN SEMARANG SELATAN: * - ikhsan gunawan (Universitas Pasir Pengaraian, 2021)
Soybean is a commodity that is rich in protein and acts as a source of vegetable protein which is very important for the body. Soybeans demand continues to increase due to the high demand for processing industry activities. The research was aimed to identify the tempeh industry profile and analyze the factors that influence the demand for soybeans in tempeh industry in South Semarang District. The research was conducted in July 2018 in South Semarang District. Slovin method used for sampling method with total sample of 89 respondent and proportionally in 10 existing sub-district. Data analysis using multiple regression analysis. The results showed that the majority of tempeh craftsmen in South Semarang are in the productive age for work, dominated by high school graduates, and the average experience is 17.5 years. Simultaneously the soybean price variable, the price of supporting goods, business capital, income, and the price of tempe had a significant effect on the demand for soybeans in the tempe industry in South Semarang District. While partially, the variable price of soybean, the price of supporting goods, and income has a significant effect soybean demand in the tempe industry in South Semarang District. The value of the price elasticity is less than one, so the elasticity is inelastic. The value of income elasticity is positive, this indicates that the normal goods are soybeans.